2010
DOI: 10.1292/jvms.09-0564
|View full text |Cite
|
Sign up to set email alerts
|

Tumors Associated with Avian Leukosis Virus Subgroup J in Layer Hens during 2007 to 2009 in China

Abstract: ABSTRACT. In the 3 years leading up to November 2009, 6 different types of naturally occurring neoplasms associated with avian leukosis virus subgroup J (ALV-J) were diagnosed by histopathology, polymerase chain reaction (PCR) and immunohistochemistry (IHC) in 140 layer hens out of approximately 100,000. The most prevalent tumor type was hemangioma (50%) in commercial layer flocks; the second most prevalent neoplasm type was myelocytoma (38.6%); a small number of ALV-J positive lymphomas (4.3%) that were not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 16 publications
3
60
0
Order By: Relevance
“…Although an intact E element was not a critical requirement for the ALV-J induction of tumors, the presence of the E element could be associated with a higher frequency of tumors in susceptible chickens (8). The ALV-Js isolated from layer flocks induced a high incidence of hemangioma in China (6,36). However, previous studies indicated that the dominant tumor induced by ALV-J infection in meat-type chickens was a myelocytoma (ML) (21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although an intact E element was not a critical requirement for the ALV-J induction of tumors, the presence of the E element could be associated with a higher frequency of tumors in susceptible chickens (8). The ALV-Js isolated from layer flocks induced a high incidence of hemangioma in China (6,36). However, previous studies indicated that the dominant tumor induced by ALV-J infection in meat-type chickens was a myelocytoma (ML) (21).…”
Section: Discussionmentioning
confidence: 99%
“…However, in China, the host range of ALV-J is changing. ALV-J has become a major problem in layer chickens since 2008 (6,14). In the present study, the analysis of sequences of ALV-J layer isolates showed that (i) the env genes of 77.8% (21/27) of the layer isolates with a high degree of genetic variation were significantly different from the env genes of the ALV-J broiler isolates, (ii) a 205-bp deletion in the 3= UTR and unique nucleotide mutations in the 3= UTR and 3= LTR were detected, and (iii) almost all layer isolates contained a complete E element of 147 to 149 residues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since it was first isolated in the UK in 1991 (Payne et al, 1991), ALV-J has spread rapidly worldwide. Moreover, the pathogenicity of ALV-J has increased in China in recent years and has induced a greater diversity of tumours compared with the ALV-J prototype virus, HPRS-103, such as myeloid leukosis, haemangioma, histiocytic sarcoma, fibrosarcoma and erythroblastoma in both broilers and layers (Cheng et al, 2010;Gao et al, 2010Gao et al, , 2012Ji et al, 2012;Lai et al, 2011;Pan et al, 2011;Qu et al, 2012;Shi et al, 2011). Although a series of programmes monitoring ALV-J surveillance and control have been conducted in China, the epidemic status is still particularly serious among indigenous Chinese chicken breeds (Dong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%